Influencing factors and mechanism of action in the pathogenesis of diffuse glomerulonephritis - Parodi B., Félix S. (1957)
I have addressed in this paper, report the etiopatogerio of acute diffuse glomerulonephritis and after chronic sick diffuse glomerulonephritis, and specify some of the causes that have led or accelerated passage in the chronic form of inadequate kidney.